2015
DOI: 10.1149/2.0891507jes
|View full text |Cite
|
Sign up to set email alerts
|

Ag/Sn Nanoparticles Reduced by Tin(II) Pyrophosphate, Tin(II) Oxalate, and Tin(II) Sulfate for Catalyzing Electroless Copper Deposition

Abstract: Different-sized Ag/Sn nanoparticles were prepared using various tin salts, including tin(II) pyrophosphate, tin(II) oxalate, and tin(II) sulfate, and applied as activators for electroless copper deposition. The transmission electron microscopy and X-ray photon electron spectroscopy data showed Ag nanoparticles of 8.2 and 10.2 nm were prepared and coated by SnO x when tin(II) sulfate and tin(II) oxalate were used, respectively. When tin(II) pyrophosphate was employed, 5.8 nm Ag nanoparticles with a thicker shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Activation is an indispensable process for electroless copper deposition, in which the copper ions are reduced by the reducing agent, and the activator (catalyst) acts as the medium transferring electrons from the reducing agent to the copper ions. , The excellent catalytic activity of Pd for the ECD reaction makes the Pd-based activation technology the most common application in the contemporary ECD industry. Nevertheless, it is the high material cost of Pd that makes the idea of exploring the cost-efficient alternatives attractive. , It is well-established that, in addition to Pd, the transition metals including Au, Ag, and Cu also exhibit different degrees of catalytic activity toward the ECD reaction . Interestingly, some investigations indicated that Ag-based catalysts can be prepared similar to the formation of conventional Sn/Pd colloidal catalyst, , and recently, copper patterns fabricated with printing technology and the ECD process that applies Ag as catalyst were also reported. , Consequently, Ag as a promising alternative to Pd in catalyzing the ECD reaction is worthy of attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation is an indispensable process for electroless copper deposition, in which the copper ions are reduced by the reducing agent, and the activator (catalyst) acts as the medium transferring electrons from the reducing agent to the copper ions. , The excellent catalytic activity of Pd for the ECD reaction makes the Pd-based activation technology the most common application in the contemporary ECD industry. Nevertheless, it is the high material cost of Pd that makes the idea of exploring the cost-efficient alternatives attractive. , It is well-established that, in addition to Pd, the transition metals including Au, Ag, and Cu also exhibit different degrees of catalytic activity toward the ECD reaction . Interestingly, some investigations indicated that Ag-based catalysts can be prepared similar to the formation of conventional Sn/Pd colloidal catalyst, , and recently, copper patterns fabricated with printing technology and the ECD process that applies Ag as catalyst were also reported. , Consequently, Ag as a promising alternative to Pd in catalyzing the ECD reaction is worthy of attention.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 It is well-established that, in addition to Pd, the transition metals including Au, Ag, and Cu also exhibit different degrees of catalytic activity toward the ECD reaction. 36 Interestingly, some investigations indicated that Ag-based catalysts can be prepared similar to the formation of conventional Sn/Pd colloidal catalyst, 37,38 and recently, copper patterns fabricated with printing technology and the ECD process that applies Ag as catalyst were also reported. 29,39 Consequently, Ag as a promising alternative to Pd in catalyzing the ECD reaction is worthy of attention.…”
Section: ■ Introductionmentioning
confidence: 99%